2020
DOI: 10.2174/1573408016666200414153108
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antioxidant and α-Glucosidase Inhibitory Activities of Indian Medicinal Plants

Abstract: Background and objective: Chronic diseases are associated with low-grade inflammation and oxidative damage. Traditional medicines have been used to manage these disorders due to their high polyphenol content and potent antioxidant activity. We evaluated the in-vitro anti-diabetic and antioxidant potential of extracts of several medicinal plants namely, Mangifera indica, Terminalia arjuna, Moringa oleifera, Albizia lebbeck, Terminalia chebula and Hippophae rhamnoides. Methods: Total polyphenol, flavonoid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…Quercetin is a potent inhibitor of intestinal GLUT2, substantially reducing glucose absorption [69]. Quercetin has repeatedly been reported to inhibit yeast α-glucosidases more so than acarbose [42,50,[70][71][72]. In contrast, for rat maltase and sucrase, it was shown to be weaker than acarbose (IC 50 = 281.2 µM for maltase, IC 50 > 400 µM for sucrase) [52], similar to the data reported here.…”
Section: Quercetinsupporting
confidence: 84%
See 1 more Smart Citation
“…Quercetin is a potent inhibitor of intestinal GLUT2, substantially reducing glucose absorption [69]. Quercetin has repeatedly been reported to inhibit yeast α-glucosidases more so than acarbose [42,50,[70][71][72]. In contrast, for rat maltase and sucrase, it was shown to be weaker than acarbose (IC 50 = 281.2 µM for maltase, IC 50 > 400 µM for sucrase) [52], similar to the data reported here.…”
Section: Quercetinsupporting
confidence: 84%
“…At the molecular level, the binding between hydroxyls in ring A, B or C of flavonoids to the active sites of α-glucosidases leads to structural changes in the enzyme evidenced by several docking studies with yeast α-glucosidase [20,55,72,79]. The inhibitory activity of flavonoids was concluded to be in the decreasing order of anthocyanidin ≥ isoflavone ≥ flavonol ≥ flavone ≥ flavonone ≥ flavan-3-ol [50], indicating the crucial role of A ring hydroxylation for potent α-glucosidases inhibition [80].…”
Section: Structure-function Relationshipsmentioning
confidence: 99%
“…The 50% ethanolic extract of Mangifera indica (MESK) was characterized using various colorimetric and analytical methods, and the results are published elsewhere [ 21 ]. In brief, the total polyphenol, flavonoid, and saponin content of MESK were 187.9 ± 14.5 µg/mg, 160.4 ± 6.2 µg/mg, and 8.3 ± 0.15 µg/mg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the total polyphenol, flavonoid, and saponin content of MESK were 187.9 ± 14.5 µg/mg, 160.4 ± 6.2 µg/mg, and 8.3 ± 0.15 µg/mg, respectively. In vitro studies suggested that MESK was a strong inhibitor of α-glucosidase and possesses significant antioxidant properties in 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging assay [ 21 ]. We tentatively identified Gallic acid, Ethyl gallate, Cinnamic acid, and Catechin as some of the phytoconstituents in MESK using mass spectroscopy [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation